2019
DOI: 10.3389/fsufs.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds for 3D Cell Culture and Cellular Agriculture Applications Derived From Non-animal Sources

Abstract: For decades, two-dimensional cell culture has been regarded as a major tool in cellular and molecular biology due to its simplicity, reproducibility and reliable nature. However, it is now recognized that 2D cell culture underrepresents the in vivo environment of living cells. The development and use of 3D scaffolds and biomaterials provide researchers an ability to more closely mimic the in vivo environment. However, many biomaterials are of animal origin, leading to variability, environmental and ethical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 138 publications
(170 reference statements)
0
72
0
1
Order By: Relevance
“…Recently, Muraro et al reported high cell viability and maintenance of ER expression up to 14 days in culture, when combining a collagen scaffold and a medium perfusion system [8]. Nonetheless, this methodology supports BC tissue maintenance by taking advantage of collagen scaffolds, biologically active animal-derived biomaterials which bring variability, as well as environmental and ethical concerns [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Muraro et al reported high cell viability and maintenance of ER expression up to 14 days in culture, when combining a collagen scaffold and a medium perfusion system [8]. Nonetheless, this methodology supports BC tissue maintenance by taking advantage of collagen scaffolds, biologically active animal-derived biomaterials which bring variability, as well as environmental and ethical concerns [11].…”
Section: Introductionmentioning
confidence: 99%
“…As animal-derived matrices have to deal with xenogenic and ethical issues [ 36 ], plant-derived matrices are a worthy option. Matrices obtainable via plant tissue decellularization [ 37 ] are extremely challenging in the tissue engineering field and scaffolding for 3D cell cultures, however, they could need smart functionalization because of some lack of biochemical mammalian cues [ 38 ]. Strategically, plant-derived scaffolds and decellularized matrices [ 39 ] are biocompatible [ 40 ], bioprintable [ 41 ], and suitable to induce human stem cell differentiation [ 42 ] like osteogenesis from induced pluripotent stem cells (iPSCs).…”
Section: Biomaterials: Overview Of Natural Polymersmentioning
confidence: 99%
“…Moreover, such fabrication routes only make use of materials of synthetic nature and are thus free from ethical concerns and of general interest in the eld. 37 In future, ethical concerns could be further minimized by the application of induced stem cellderived neurons which have been demonstrated to be cultivatable on microstructured substrates as well. 38,39 In this work, we combine established technologies, namely grayscale lithography (GSL) and ultraviolet nano-imprint lithography (UV-NIL) with reactive ion etching (RIE) to prepare readily reproducible and cost-effective modulated surfaces.…”
Section: Introductionmentioning
confidence: 99%